2022
DOI: 10.3390/jcm11051412
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Efficacy of Regdanvimab on Clinical Outcomes in Patients with Mild to Moderate COVID-19

Abstract: Background: This study aims to evaluate the real-world effectiveness of regdanvimab on clinical outcomes in patients with mild to moderate coronavirus disease 2019 (COVID-19). Methods: This retrospective observational study included 152 patients (89 received regdanvimab and 63 did not) diagnosed with mild to moderate COVID-19 between August 2021 and October 2021 and admitted to Armed Forces Goyang Hospital. We collected information on the use of regdanvimab, remdesivir, dexamethasone, and supplemental oxygen; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The electronic search identified a total of 7 studies 2 , 4 , 5 , 6 , 7 , 8 , 9 , one of which were randomized controlled trials and the others were retrospective studies. This meta-analysis included 1350 patients in the regdanvimab group, 1983 patients in the control group.…”
mentioning
confidence: 99%
“…The electronic search identified a total of 7 studies 2 , 4 , 5 , 6 , 7 , 8 , 9 , one of which were randomized controlled trials and the others were retrospective studies. This meta-analysis included 1350 patients in the regdanvimab group, 1983 patients in the control group.…”
mentioning
confidence: 99%
“…Out of a total of 138 studies after removing duplicates, 12 full-text studies were assessed for eligibility. Four studies were excluded due to irrelevant data, 22,27 combination therapy 28 or review article. 29 Finally, 8 studies 16,20,21,[30][31][32][33][34] including 2 RCTs 16,32 and 6 observational studies 20,21,30,31,33,34 with 4793 patients were considered in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…This finding is consistent with the pooled estimate of six studies, which demonstrated the effectiveness of sotrovimab in decreasing the need for mechanical ventilation due to COVID-19 [ 23 ]. The existing literature also suggests that other mAb therapies, such as regdanvimab [ 28 ] and casirivimab/imdevimab, may be effective in reducing the need for supplemental oxygen therapy and mechanical ventilation in patients with COVID-19, compared to control participants.…”
Section: Discussionmentioning
confidence: 99%